(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This artcle analyzes the consistent measures implemented in Uzbekistan to develop physical education and sports, create the necessary conditions and infrastructure for promoting a healthy lifestyle-especially among the youth-and ensure the nation’s active participation in international sports arenas. It highlights the pedagogical, psychological, and health-promoting significance of physical education and sports in shaping a healthy, well-rounded, and socially active generation. The paper also underscores the impact of regular physical exercise on enhancing cognitive performance, increasing labor productivity, strengthening occupational health, and the importance of medical–pedagogical supervision as a safeguard for effective and safe training.